"DAKLI": a multipurpose ligand with high affinity and selectivity for dynorphin (kappa opioid) binding sites. - Goldstein, A (1988)
We describe a synthetic ligand, "DAKLI" (Dynorphin A-analogue Kappa LIgand), related to the opioid peptide dynorphin A. A single reactive amino group at the extended carboxyl terminus permits various reporter groups to be attached, such as 125I-labeled Bolton-Hunter reagent, fluorescein isothiocyanate, or biotin. These derivatives have high affinity and selectivity for the dynorphin (kappa opioid) receptor. An incidental finding is that untreated guinea pig brain membranes have saturable avidin binding sites.